Border-Zone Infarction Due to Cerebrovascular Fibromuscular Dysplasia - Yu-Ming Chen (Diagnostics, 2022)
A 45-year-old male presented with acute-onset left-sided weakness and slurred speech. Non-contrast-enhanced brain magnetic resonance imaging revealed cortical and internal border-zone infarcts compatible with stroke. A survey of ischemic stroke risk factors in young adults excluded coagulopathy, vasculitis, and cardiac disease. Nevertheless, neck-computed tomography angiography revealed a long-segmental narrowing of the right internal carotid artery with wall thickening and a “string-of-beads” appearance suspicious for fibromuscular dysplasia, which was confirmed on further angiography. His clinical condition stabilized after intensive medical therapy. This case demonstrates cerebrovascular fibromuscular dysplasia as a possible cause of ischemic stroke in young adults.